Reliable and confidential cloud storage with efficient data forwarding functionality - Liu, Jian; Wang, Huimei; Xian, Ming; Rong, Hong; Huang, Kun (IET communications, 2016)
Cloud computing is a promising computing paradigm which has drawn extensive attention. Serious concerns over the reliability and confidentiality of the outsourced data are arising. Traditional encryption methods can, guarantee data confidentiality, however, it also limits the cloud's functionality as few operations are supported over encrypted data. In this study, the authors construct an enhanced cloud that not only provides secure and robust data storage, but also supports the functionality that the cipher data can be forwarded without being retrieved back. Specifically, they design an all-or-nothing-transform-based encryption and a variant of ElGamal-based proxy re-encryption algorithms, blending them with Reed–Solomon code, the authors’ scheme is quite more efficient compared with previous studies because it only needs to update partial data blocks instead of the whole file for data forwarding. Besides, the authors’ scheme also satisfies another practical property that the original data owner can no longer decrypt or forward the re-encrypted data to others after a complete forwarding instance, which is termed to be ‘original inaccessibility’ in this study. Analysis shows that the authors’ scheme is secure and satisfactory. Finally, the authors theoretically and experimentally evaluate its performance and the results indicate that their scheme is efficient during file dispersal, forward and retrieval.